2018
DOI: 10.4067/s0718-58392018000300318
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression and performance of partially self-fertilized maize progenies in a top cross

Abstract: Information on the effect of endogamy and combining ability of inbred families is essential in hybrid maize (Zea mays L.) breeding programs. The objective of this study was to evaluate the effect of inbreeding in a maize population and the performance of top-cross hybrids from this population, with a broad genetic base tester. First, 110 S1 families were generated and established in the field along with families from the original population. The experiment was arranged in a randomized block design with three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
3
1
0
1
Order By: Relevance
“…The inbreeding depression (ID%) for the grain yield trait was, on an average, 30.89%, and it ranged from 17.42 to 46.09% for the hybrids AG1051 and RK3014, respectively (Table 7). Other results corroborate with the values obtained in this work (Oliveira et al, 2020;Somera et al, 2018).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The inbreeding depression (ID%) for the grain yield trait was, on an average, 30.89%, and it ranged from 17.42 to 46.09% for the hybrids AG1051 and RK3014, respectively (Table 7). Other results corroborate with the values obtained in this work (Oliveira et al, 2020;Somera et al, 2018).…”
Section: Resultssupporting
confidence: 93%
“…When considering the contribution of the estimates for plant height, it is observed on an average, as a higher contribution of m+a (80.43%) in relation to d (19.57%) (Table 8). Similar results were reported by several authors demonstrating that this characteristic has a greater influence of additive effects than others (Oliveira et al, 2020;Somera et al, 2018;Viana et al, 2009).…”
Section: Resultssupporting
confidence: 92%
“…Results in Table 4a and b reflecting that dominance plays greater role in inheritance of most studied traits, so selection for improvement these traits could be effective in late generations. Additive x additive gene effect was more effective than dominance x dominance and additive x dominance reflecting the important of this type of gene action, similar results were obtained by Mansour [22], Andreia et al [24] and Attiq et al [21]. Bojan et al [28] reported that, dominant was more important than additive component.…”
Section: Discussionsupporting
confidence: 72%
“…Little information is available on obtaining cultivars for green maize production, and there are few genetic studies on the traits involved in this production (Kuki et al, 2017;Somera et al, 2018). Most studies are evaluation of the performance of existing cultivars (Cardoso et al, 2004;Lima et al, 2019;Couto et al, 2017;Rodrigues et al, 2018).…”
Section: Introductionmentioning
confidence: 99%